2018
DOI: 10.1002/lno.11049
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling limnological processes in the time‐frequency domain

Abstract: State variables in lake ecosystems are subject to processes that act on different time scales. The relative importance of each of these processes changes over time, e.g., due to varying constraints of physical, biological, and biogeochemical processes. Correspondingly, continuous automatic measurements at high temporal resolution often reveal intriguing patterns that can rarely be directly ascribed to single processes. In light of the rather complex interplay of such processes, disentangling them requires more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 82 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…The high‐frequency in‐stream monitoring efforts at the Pallas catchment enable the use of new methods of data analysis such as wavelet transform (Crawford et al, 2017; Riml et al, 2019; Schmidt et al, 2019), which can improve knowledge of carbon sources and related hydrological connectivity in subarctic catchments (Figure 4(b)–(d)). For example, Figure 4(b) shows the development of diurnal periodicity in TOC dynamics after snowmelt begins, which likely reflects the onset of increased microbial activity and greater in‐stream processing of TOC as stream temperatures become warmer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high‐frequency in‐stream monitoring efforts at the Pallas catchment enable the use of new methods of data analysis such as wavelet transform (Crawford et al, 2017; Riml et al, 2019; Schmidt et al, 2019), which can improve knowledge of carbon sources and related hydrological connectivity in subarctic catchments (Figure 4(b)–(d)). For example, Figure 4(b) shows the development of diurnal periodicity in TOC dynamics after snowmelt begins, which likely reflects the onset of increased microbial activity and greater in‐stream processing of TOC as stream temperatures become warmer.…”
Section: Resultsmentioning
confidence: 99%
“…The high-frequency in-stream monitoring efforts at the Pallas catchment enable the use of new methods of data analysis such as wavelet transform (Crawford et al, 2017;Riml et al, 2019;Schmidt et al, 2019), which can improve knowledge of carbon sources and related hydrological connectivity in subarctic catchments (Figure 4 . This relationship between discharge and TOC suggests that discharge and TOC increase concurrently in snowmelt season at longer-term periodicities, thereby indicating that the process which increases flow across this timescale may be linked to the process which increases TOC.…”
Section: High-frequency In-stream Toc Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional approaches to resolving aquatic transport problems are based on assessments of hydrochemical observations in the time domain. However, novel approaches transforming the problem into the frequency domain have emerged, allowing to analyze temporal patterns (Crawford et al, 2017;Kirchner & Neal, 2013;Schmidt et al, 2018;Weigand et al, 2017;Yan et al, 2017) and provide quantitative estimates of transport rates (Godsey et al, 2010;Guan et al, 2011;Riml & Wörman, 2015) as functions of the inherent time scales of the observed dynamics. The Fourier representation is a way to complement time domain analyses that unlocks new possibilities to utilize high-frequency hydrochemical observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, while increasing water temperatures and riverine inputs due to climate change have been frequently observed (e.g., Isles et al., 2017 for Lake Champlain), and the mechanisms for climate change synergistically interacting with legacy nutrient reserves are well‐established (e.g., Nazarai‐Sharabian et al., 2018; Orihel et al., 2017), we are not aware of observational studies that have conclusively demonstrated such an effect over time. This is partly because it can be difficult to disentangle internal versus external drivers of change in highly dynamic shallow lake systems (Schmidt et al., 2019).…”
Section: Introductionmentioning
confidence: 99%